Introduction to continuous-time stochastic processes theory, models, and applications to finance, biology, and medicine - Capasso Vincenzo; Bakstein David (Boston Birkhauser, 2005)
This concisely written book is a rigorous and self-contained introduction to the theory of continuous-time stochastic processes. A balance of theory and applications, the work features concrete examples of modeling real-world problems from biology, medic
Keywords: Stochastic processes